Knowledge, attitudes and peer influences related to pregnancy, sexual and reproductive health among adolescents using maternal health services in Ugu, KwaZulu-Natal, South Africa - Desiree Govender; Saloshni Naidoo; Myra Taylor (BMC, 2019)
Abstract Background Knowledge and practices of sexual and reproductive healthcare is pivotal to the Safe Motherhood Initiative; however, only a few studies have investigated adolescent mothers' knowledge of sexual and reproductive health in light of the above initiative. Research should thus focus on the knowledge and attitudes of adolescent girls as well as peer influences related to pregnancy and sexual and reproductive health among adolescents, as the findings may highlight vital health interventions that should be introduced. The aim of this study was thus to determine the knowledge, personal attitudes and peer influences related to pregnancy, sexual and reproductive health among adolescents who attended maternal health services in a district hospital in Ugu, KwaZulu-Natal, South Africa. Methods A cross sectional study was conducted. Data were collected from 326 adolescents who accessed maternal health services in a peri-urban district hospital during June 2017 and November 2017. The questionnaire surveyed the knowledge, personal attitudes and peer influences related to pregnancy, sexual and reproductive health. The questionnaire was administered by fieldworkers using mobile devices powered by the Mobenzi Researcher® technology. The completed surveys were uploaded to the Mobenzi server where it was stored and aggregated. The data was analysed using R software. Results Of the 326 participants, 65 (19.9%) experienced repeat pregnancies in adolescence. Overall, only 143 (43.9%) of the participants answered 50% or more of the knowledge questions on pregnancy and HIV/AIDS and STIs correctly, while 183 (56.1%) answered less than 50% of the knowledge questions correctly. There was no relationship between knowledge of pregnancy and HIV/STIs and repeat adolescent pregnancies. Conclusion Adolescents' knowledge of pregnancy and sexual and reproductive health was deficient as, even with repeat pregnancies, these adolescents were evidently no better informed about pregnancy and sexual and reproductive health. This suggests that social determinants, modes and platforms regarding the delivery of adolescent sexual and reproductive health education are important. An innovative mode to the delivery of sexual and reproductive health education includes the emerging digital platform. The digital platform encompasses social media, multimedia and mobile phones which is growing popular among young people.